Comparison of C-4DST and F-FDG PET/CT imaging for advanced renal cell carcinoma: preliminary study. - Minamimoto, Ryogo; Nakaigawa, Noboru; Nagashima, Yoji; Toyohara, Jun; Ueno, Daiki; Namura, Kazuhiro; Nakajima, Kazuhiko; Yao, Masahiro; Kubota, Kazuo (Abdominal Radiology, 2016)
Purpose: 4′-[Methyl-C]-thiothymidine (4DST) has been developed as an in vivo cell proliferation marker based on its DNA incorporation mechanism. This study evaluated the potential of 4DST PET/CT for imaging cellular proliferation in advanced clear cell renal cell carcinoma (RCC), compared with FDG PET/CT. Both 4DST and FDG uptake were compared with biological findings based on surgical pathology. Methods: Five patients (3 men and 2 women; mean (±SD) age 64.8 ± 11.0 years) with a single RCC (mean diameter: 9.3 ± 3.2 cm) were examined by PET/CT using 4DST and FDG. The dynamic emission scan of 4DST for RCC over 35 min followed by a static emission scan of the body for 4DST and FDG. Then we compared the maximum standardized uptake value (SUVmax) of 20 areas of RCC on both 4DST and FDG images with (1) the Ki-67 index of cellular proliferation (2) Fuhrman grade system for nuclear grade (G) in RCC and (3) pathological phosphorylated grade of mammalian target of rapamycin (pmTOR). Results: All patient cases showed clear uptake of FDG and 4DST in RCC tumors, with mean 4DST SUVmax of 7.3 ± 2.2 (range 4.3-9.4) and mean FDG SUVmax of 6.0 ± 2.8 (range 3.4-10.4). The correlation coefficient between SUVmax and Ki-67 index was higher with 4DST ( r = 0.61) than with FDG ( r = 0.43). Tumor 4DST uptake (G0: 1.4, G2: 2.6, G2 5.6, G4: 5.7) and tumor FDG uptake (G0: 1.8, G2: 2.9, G2 3.7, G4: 4.1) were both related to Fuhrman grade system. The 4DST uptake increased as the pmTOR grade increases (G0: 3.1, G1: 4.8, G2: 4.7, G3: 6.2); in contrast FDG uptake was unrelated to pmTOR grade (G0: 2.8, G2: 4.0, G2 3.3, G4: 3.6). Conclusion: A higher correlation with the proliferation of RCC was observed for 4DST than for FDG. The 4DST uptake exhibits the possibility to predict pmTOR grade, indicating that 4DST has potential for the evaluation of therapeutic effect with mTOR inhibitor in patients with RCC.